Some thoughts on proper terminology - Newton, H. (coachesinfo.com)
English-speakers have, over the years, introduced a number of expressions to describe different disciplines or practices related to resistance training. Since this activity is so popular with coaches, athletes, sport scientists, medical professionals, members of the lay public, and the sports media, it is done them all a disservice by the continued failure to properly identify these activities. That's why this article... Some terms are explained.